Clinical findings and provision of care in haemodialysis patients with chronic itch: new results from the German epidemiological haemodialysis itch study - Hayani, Kinan; Weiß, Melanie; Weisshaar, Elke (Acta dermato-venereologica, 2016)
The German Epidemiological Haemodialysis Itch Study (GEHIS) has shown that more than one-third of ha...
Epub ahead of print Nov 9, 2015
Gesehen am 07.05.2020